Theoretical foundations of strategic motivation in the works of Nobel laureates - O. A. Fesyanova (Управленческое консультирование)
The purpose of the article is to expand the existing theoretical and applied understanding of strategic motivation by identifying certain aspects of this issue in the scientific works of Laureates of the Nobel Memorial Prize in Economic Sciences (officially known as The Sveriges Riksbank Prize in Economic Sciences in Memory of Alfred Nobel) in the period from 2000 to 2022.The introduction discusses the differences in the understanding of the terms “strategic motivation” and “motivation” in the works of domestic and foreign scientists and practitioners, notes a long-term, future-oriented understanding of strategic motivation and its difference from the predominantly operational nature of motivation in the understanding of the classics of management science. The main part of the article sequentially analyzes the lectures and additional materials of the award committee, scientific articles, books and monographs of the laureates related to the research topics for which the award was awarded. The analysis highlights the main aspects of scientists’ research related to strategic motivation, its place and significance in the process of developing and implementing a strategy. Intermediate conclusions are made about the views and positions on the topic under consideration of each laureate, whose work was analyzed in the article. At the end of the article a general conclusion is formulated about the relevance and interdisciplinary (at the intersection of the natural sciences and liberal arts) nature of the issue of strategic motivation, emphasis is placed on the emerging trend towards considering predominantly non-material, psychological and behavioral aspects of the subject under study, the role of innovation in stimulating micro- and macro-levels. The conclusion is made about how it is possible to expand and supplement the existing understanding of strategic motivation taking into account the considered materials. It is noted that the conclusions made on the basis of the analysis can be applied in further research, as well as in practice when creating a system of strategic motivation in enterprises.The analysis is based on the theory of strategy and methodology of strategizing of the Foreign Member of the Russian Academy of Sciences (Life-time), Dr. Sc. (Econ.), Vladimir L. Kvint.